Environmental Impacts of the China-Pakistan Economic Corridor (CPEC): An analysis of Climate Change Mitigation and Adaptation Strategies - Munir, Muhammad Munir; Hussain, Raziq; Ahmad, Munir (MultiTech Publisher, 2024)
This article explores the complex environmental impacts of the China-Pakistan Economic Corridor (CPEC) and suggests sustainable development strategies. Our study reveals significant changes in land use patterns, including loss of important habitat, which is contributing to biodiversity decline. Analysis of air quality data shows increased levels of pollutants in urban areas along the corridor, which are exacerbated by construction activity and increased traffic. Water resource assessments highlight issues related to quality and availability, especially in areas with high industrial activity. In response to these findings, we suggest methods for mitigating and adapting to climate change along the corridor. Interpreting these findings, we argue that these assessments are critical for identifying potential environmental problems and ensuring that development initiatives are built with long-term sustainability in mind. Recommendations for mitigating climate change include international cooperation, increasing public awareness, and using resilient design principles. For future development projects, we include sustainable practices, community involvement and compliance with environmentally friendly standards as important elements in economic growth. We draw conclusions by emphasizing the need for future studies to track long-term impacts, evaluate socio-economic implications, and implement environmentally friendly strategies, maintaining a long-term balance between economic development and environmental conservation in CPEC and other international projects.